The Mediating Role of the TPB in the Relationship Between Entrepreneurship Education and Entrepreneurial Intention Among Indonesian Undergraduate Students - Novika Candra Astuti; Ismail Solihin (Asia Pacific Journal of Management and Education (APJME), 2024)
The objective of this study is to analyze the effects of entrepreneurship education on students' attitudes, social norms, and perceived behavioral control, and how these elements impact entrepreneurial intentions using the Theory of Planned Behavior (TPB) model. University students enrolled in entrepreneurship programs in Bandung, Indonesia, were surveyed. The study employed Partial Least Squares Structural Equation Modelling (PLS-SEM) using Smart PLS software to test the theoretical model. The study confirms that entrepreneurship education positively impacts students' attitudes (H1), social acceptance (H2), and perceived control (H3) toward entrepreneurial careers. However, attitude and social acceptance do not significantly affect entrepreneurial intention (H4 H5), while perceived control strongly enhances entrepreneurial intention (H6). The impact of entrepreneurship education on intention is indirect, with social acceptance and perceived control serving as effective mediators (H9, H10), while attitude does not mediate this relationship (H8). The study concludes that entrepreneurship education fosters entrepreneurial ambition indirectly through perceived behavioral control and social acceptance. Universities and policymakers should focus on improving both the social and practical aspects of entrepreneurial education to enhance students' entrepreneurial aspirations.